Retinitis Punctata Albescens and RLBP1-Allied Phenotypes - Béatrice Bocquet, PhD; Hicham El Alami Trebki, MD; Anne Françoise Roux, PharmD, PhD; Gilles Labesse, PhD; Philippe Brabet, PhD; Carl Arndt, MD, PhD; Xavier Zanlonghi, MD; Sabine Defoort-Dhellemmes, MD; Dalil Hamroun, PhD; Céline Boulicot-Séguin, MD; Léopoldine Lequeux, MD; Marie Christine Picot, MD; et al. (Ophthalmology Science, 2021)
Purpose: To identify relevant criteria for gene therapy based on clinical and genetic characteristics of rod–cone dystrophy associated with RLBP1 pathogenic variants in a large cohort comprising children and adults. Design: Retrospective cohort study. Participants: Patients with pathogenic variants in RLBP1 registered in a single French reference center specialized in inherited retinal dystrophies. Methods: Clinical, multimodal imaging, and genetic findings were reviewed. Main Outcome Measures: Age of onset; visual acuity; ellipsoid line length; nasal, temporal, and foveal retinal thickness; and pathogenic variants and related phenotypes, including Newfoundland rod–cone and Bothnia dystrophies (NFRCDs), were reappraised. Results: Twenty-one patients (15 families) were included. The most frequent form was NFRCD with 12 patients (8 families) homozygous for the recurrent deletion of exons 7 through 9 in RLBP1 and 5 patients (4 families) with biallelic protein-truncating variants (2 novel: p.Gln16∗ and p.Tyr251∗). A novel combination of the p.Arg234Trp Bothnia variant with a nonsense variant in trans led to Bothnia dystrophy in 2 sisters. One proband carrying the p.Met266Lys Bothnia variant and in trans p.Arg121Trp and a second, with the p.Arg9Cys and p.Tyr111∗ combination, both demonstrated mild retinitis punctata albescens. Independently of genotype, all patients showed a visual acuity of worse than 20/200, an ellipsoid line width of less than 1000 μm, and a mean foveal thickness of less than 130 to 150 μm, with loss of both the interdigitation and ellipsoid lines. Conclusions: The eligibility for RLBP1 gene therapy first should be determined according to the biallelic variant combination using a robust classification as proposed herein. An ellipsoid line width of more than 1200 μm and a central thickness of more than 130 to 150 μm with detectable ellipsoid and interdigitation lines should be 2 prerequisite imaging indicators for gene therapy.